Cleaning up and invigorating the civil service - Klitgaard, Robert (1997)
Reliable quantitative estimates are not available of: (1) the quality of civil service performance and changes therein as the result of development projects, or (2) the importance of civil service performance for various development outcomes. Nonetheless, anecdotal evidence indicates that in some countries government performance has indeed collapsed, with calamitous effects on development. Although poor government performance is theoretically overdetermined there are many possible causes, which we cannot disentangle in practice - a plausible story to be told based on institutional economics, using such concepts as information, incentives, a credible commitment. This version of both problems and solutions is supported by example of successful reforms. The article argues that "institutional adjustment" deserves more consideration as a basis for reforms. Two practical examples are discussed in some detail improving incentives in the public sector and strategies to combat corruption. - Reproduced
Keywords: Civil service reform; Civil service